Jurnal Penyuluhan: Motivasi Petani dalam Pengelolaan Usaha Hutan Rakyat Desa Cingambul, Kecamatan Cingambul, Majalengka - Suherdi Suherdi, Siti Amanah, Pudji Muljono (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Private forests have economical, social and environmental benefits. Through the private forests, farmers can support the fulfillment of the household needs, included basic and social needs, as well as appreciation for their initiatives and actions in land rehabilitation. Without strong motivation from farmers, the private forests would be rarely found. Thus, the research objective is to analyze factors motivate farmers do the business and therole of the forests extension workers in the development of private forests.